Unilateral Zygomatic Complex Fracture – A Comparison Between Nonsurgical Treatment and Surgical Treatment. Issue 7 (October 2021) - Ling, Xiao Feng; Yew, Ching Ching; Mohd Nazri, Syakiroh bt; Tew, Mei Mei
Abstract : Background: Medical advances have enabled zygomatic complex (ZMC) fractures to be treated by various approaches. This study aims to analyze the demographics and treatment outcomes of unilateral ZMC fractures, treated nonsurgically or surgically. Methods: This 5-year nonrandomized prospective study had included 65 cases of unilateral ZMC fractures from October 2014 until December 2019. Patients were treated and divided into nonsurgical and surgically treated group. Treatment outcomes in terms of step deformities, malar depression, diplopia, infraorbital hypoaesthesia, and mouth opening were evaluated up to six months post-trauma/intervention. Results: Road traffic accident (96.9%) was the main cause, with predominant male involvement (80%) and median age of 28 years. Significant improvements ( P < 0.05) were observed for step deformities and malar depression among the surgically treated group at postoperative day 1 and week 1. Throughout the six months review, infraorbital hypoesthesia and diplopia showed no significant differences between both groups, ( P > 0.05). Besides, all patients showed significant mouth opening improvement ( P < 0.05) over six months period. Conclusion: The authors found that infraorbital hypoaesthesia and limited of mouth opening should not be the absolute indications for surgical treatment of ZMC fractures. Nonsurgical treatment that included early jaw exercise and symptomatic treatment had potential value for satisfactory functional gain. Abstract : Supplemental Digital Content is available in the text